In(Ga)N Nanostructures and Devices Grown by Molecular Beam Epitaxy and Metal-Assisted Photochemical Etching - Abdul Kareem K. Soopy; Zhaonan Li; Tianyi Tang; Jiaqian Sun; Bo Xu; Chao Zhao; Adel Najar (Nanomaterials, 2021)
This review summarizes the recent research on nitride nanostructures and their applications. We cover recent advances in the synthesis and growth of porous structures and low-dimensional nitride nanostructures via metal-assisted photochemical etching and molecular beam epitaxy. The growth of nitride materials on various substrates, which improves their crystal quality, doping efficiency, and flexibility of tuning performance, is discussed in detail. Furthermore, the recent development of In(Ga)N nanostructure applications (light-emitting diodes, lasers, and gas sensors) is presented. Finally, the challenges and directions in this field are addressed.